Roles of Streptococcus mutans-Candida albicans interaction in early childhood caries: a literature review - Lu, Yifei; Lin, Yifan; Li, Mingyun; He, Jinzhi (Frontiers in Cellular and Infection Microbiology, 2023)
As one of the most common oral diseases in kids, early childhood caries affects the health of children throughout the world. Clinical investigations show the copresence of Candida albicans and Streptococcus mutans in ECC lesions, and mechanistic studies reveal co-existence of C. albicans and S. mutans affects both of their cariogenicity. Clearly a comprehensive understanding of the interkingdom interaction between these two microorganisms has important implications for ECC treatment and prevention. To this end, this review summarizes advances in our understanding of the virulence of both C. albicans and S. mutans. More importantly, the synergistic and antagonistic interactions between these two microbes are discussed.